C-reactive protein level is a prognostic indicator for survival and improves the predictive ability of the R-IPI score in diffuse large B-cell lymphoma patients - Troppan, K T (Nature Publishing Group, 2014)
BACKGROUND: High levels of C-reactive protein (CRP), an acute phase protein, proofed being associated with decreased clinical outcome in small-scale studies in diffuse large B-cell lymphoma (DLBCL). The aim of this study was to evaluate the prognostic impact of pretreatment CRP levels on overall survival (OS) and disease-free survival (DFS) in a large bicentre study of DLBCL patients. METHODS: Data from 477 DLBCL patients, diagnosed and treated between 2004 and 2013 at two Austrian centres, were evaluated retrospectively. The prognostic influence of CRP and other factors, including age, tumour stage, and revised International Prognostic Index (R-IPI) on 5-year OS and 5-year DFS, were studied by Kaplan–Meier curves as well as univariate and multivariate Cox regression models. Influence of CRP on the predictive accuracy of the R-IPI score was determined by the Harrell concordance index. RESULTS: Kaplan–Meier curves revealed elevated CRP as a factor for decreased 5-year OS and DFS in DLBCL patients (P<0.001, log-rank test). An independent significant association between high CRP levels and poor clinical outcome in multivariate analysis for 5-year OS (HR=1.51, CI 95%=1.04–2.20, P=0.031) and for DFS (HR=1.91, CI 95%=1.28–2.85, P=0.002) was found. The estimated concordance index was 0.75 using the original R-IPI score and 0.79 when CRP was added. CONCLUSIONS: In the present study, we demonstrated high CRP levels at diagnosis of DLBCL as an independent poor prognostic factor for clinical outcome. Adding CRP to the well-established prognostic models such as the R-IPI score might improve their predictive ability.